2021
DOI: 10.1186/s12909-021-02578-y
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based intervention helps preclinical medical students to contain stress, maintain mindfulness and improve academic success

Abstract: Background Stress among students is on the rise during early medical school and has been implicated in poor academic performance. Several methods are being discussed to efficiently reduce stress, among them mindfulness-based interventions. We therefore set out to assess how stress, mindfulness, and academic performance are connected and if an intervention on mindfulness based stress reduction could alleviate stress among medical students and improve their academic achievements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…The researchers found that if we pay more attention to students, we also eliminate the level of their academic stress. This finding came about from data the authors acquired through an experiment with 143 students of medicine (Lampe and Müller-Hilke, 2021).…”
Section: Research Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that if we pay more attention to students, we also eliminate the level of their academic stress. This finding came about from data the authors acquired through an experiment with 143 students of medicine (Lampe and Müller-Hilke, 2021).…”
Section: Research Conceptsmentioning
confidence: 99%
“…-Partnership Intervention (Turner and Simmons, 2020) based on communication between subjects within the academic environment and co-operation on the goals of student learning; -Stress Management Intervention based on screening endangered students and subsequent planning, organisation and co-operation in order to minimise academic stress (Sultan, Amin and Khan, 2021); and -Mindfulness-based Intervention based on the attention paid to students and observation of students (Lampe and Müller-Hilke, 2021). A question that remains in terms of intervention to minimise academic stress is the use of centres at universities designated for this purpose.…”
Section: Recommendations Provided By the Studiesmentioning
confidence: 99%
“…Mindfulness-based interventions have been studied in medical students, with promising results in terms of stress reduction [ 15 ], and improvements in wellbeing [ 16 ]. Likewise, recent evidence has demonstrated that lower perceived stress was associated with greater mindfulness, and that a brief mindfulness intervention in medical training was effective in maintaining lower perceived stress [ 17 ]. Further, a recent systematic review concluded that mindfulness is beneficial for reducing stress in medical students [ 18 ], thereby demonstrating its efficacy for medical students.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that people with high levels of mindfulness can easily recognize the judgments they make automatically, make more objective assessments, see reality as it is, and use compassionate language in place of their inner critics (Brown & Ryan, 2003). Mindfulness studies with different variables in different domains such as social life, business, professional life, and academic life has been shown to improve social skills (Manusov et al, 2020), facilitate adaptation and coping (Ghahremanlou et al, 2021), protect psychological satisfaction and physiological health (Hero, 2020), bring success in business and school life (Lampe & Müller-Hilke, 2021;Li, 2022), and increase life satisfaction (Dirzyte et al, 2022). Despite the increasing number of studies addressing the concept of mindfulness within intercultural literature (Zegarac et al, 2014), it should be noted that very few studies have been conducted on this topic.…”
Section: Introductionmentioning
confidence: 99%